Matrimonial Strategies in Transylvania. Mihály Teleki’s First Marriage. “Remember: embittered hearts are healed with wine” - GYÖRGY, Árpád-Botond (Studia Universitatis Babeș-Bolyai Historia, 2021)
The wedding and the marriage was a very important stage of early modern society life, it was not only a social event, but the boundary between childhood and adulthood. For a noble like Mihály Teleki, successful marriage helped to develop in administration and to improve economic resources. To Mihály Teleki marriage is an opportunity of upward social mobility. In this paper we discuss about these matrimonial strategies and we identify their meanings. Rezumat: Nunta şi căsătoria au fost o etapă foarte importantă a vieţii societăţii moderne timpurii, nu a fost doar un eveniment social, ci graniţa dintre copilărie şi maturitate. Pentru un nobil precum Mihály Teleki, căsătoria reuşită a contribuit la dezvoltarea în administraţie şi la îmbunătăţirea resurselor economice. Pentru Mihály Teleki o căsătorie este o oportunitate de mobilitate socială ascendentă. În această lucrare discutăm despre aceste strategii matrimoniale şi identificăm semnificaţiile acestora. Cuvinte cheie: Mihály Teleki, societate modernă timpurie, strategii matrimoniale, Transilvania.